Problematika Pertanggungjawaban Anak dalam Tindak Pidana Pembunuhan Dibandingkan dengan Pelaku Dewasa - Cahya, Afinda Cahya Saputri; Fadiya Nabila; Yudi Widagdo Harimurti (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Murder committed by children presents a dilemma in the criminal justice system, as it must balance the enforcement of justice with the protection of children's rights. This article examines the problematic nature of juvenile criminal liability in murder by comparing the perpetrator's legal approach to that of adults. Normative juridical research methods are used to explain legal provisions, court decisions, and related doctrines. The results indicate that juvenile offenders are not solely focused on their culpability but also on the child's psychological capabilities, maturity level, and social circumstances. Meanwhile, adult offenders are held fully accountable, with a focus on punishment. The main challenges are the difficulty of proving intent and the need for special mechanisms for handling juvenile offenders of serious crimes. This study provides for strengthening the capacity of law enforcement, improving child rehabilitation facilities, optimizing diversion mechanisms, and educating the public to support humane and proportional protection and enforcement of justice.